Pengiriman Data Detak Jantung Menggunakan Teknik Kompresi Pada Raspberry PI - Akbar, Nurhadi; Candra, Feri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Heart attack is one of the causes of high mortality, so a lot of research make a tool to monitor human heart activities. In this study, researchers use a Raspberry pi that is connected to the AD 8232 module. The AD 8232 module to detect heart signal, commonly called ECG signals. The AD 8232 module is connected with an ADC module to convert analog signals into digital signals that are connected to raspberry pi, then the ECG signal conduct a compression process. The compression process aims to minimize the byte of storage in the raspberry pi where as ECG signal measurements are carried out in real-time. To get the right and optimal compression method without destruct the ECG signal data, researchers compare two data compression methods. The two data compression will be used are the Huffman Code and Lempel Ziv Welch. The results of the comparison ratio of data before and after the compression process for are 43.96% huffman and 88.61% for lempel Ziv Welch.Key words: Raspberry Pi, EKG module, AD 8232 module, compression, Algoritma Huffman